The limited prosocial emotions specifier for conduct disorder among detained girls: a multi-informant approach - Damme, Lore van (Criminal justice and behavior, 2016)
This study examines the prevalence and clinical usefulness of the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5) specifier ?with Limited Prosocial Emotions? (LPE) in detained girls. Detained girls (N = 85; Mage = 16.24) and their parents were interviewed with a structured diagnostic interview to identify girls with conduct disorder (CD), and both informants completed the Antisocial Process Screening Device to assess the LPE specifier. Psychiatric disorders other than CD, aggression, and offending were assessed through standardized self-report tools. Different approaches were used to deal with diagnostic information from multiple informants. The prevalence of CD + LPE girls was lower when using self-report (12.9%) compared with parent-report (38.8%), suggesting that parents indeed are important to identify CD + LPE girls. However, including parental information did not result in a better differentiation between CD + LPE and CD-only girls. Specifically, the LPE specifier only enabled to identify a group of seriously antisocial girls with higher levels of proactive aggression, though solely when using self-report.